Cortical GABAergic Dysfunction in Stress and Depression: New Insights for Therapeutic Interventions - Fogaça, Manoela V.; Duman, Ronald S. (Frontiers in Cellular Neuroscience, 2019)
Major depressive disorder (MDD) is a debilitating illness characterized by neuroanatomical and functional alterations in limbic structures, notably the prefrontal cortex (PFC), that can be precipitated by exposure to chronic stress. For decades, the monoaminergic deficit hypothesis of depression provided the conceptual framework to understand the pathophysiology of MDD. However, accumulating evidence suggests that MDD and chronic stress are associated with an imbalance of excitation-inhibition (E:I) within the PFC, generated by a deficit of inhibitory synaptic transmission onto principal glutamatergic neurons. MDD patients and chronically stressed animals show a reduction in GABA and GAD67 levels in the brain, decreased expression of GABAergic interneuron markers and alterations in GABAA and GABAB receptor levels. Moreover, genetically modified animals with deletion of specific GABA receptors subunits or interneuron function, show depressive-like behaviors. Here we provide further evidence supporting the role of cortical GABAergic interneurons, mainly somatostatin- and parvalbumin-expressing cells, required for the optimal E:I balance in the PFC and discuss how the malfunction of these cells can result in depression related behaviors. Finally, considering the relatively low efficacy of current available medications, we review new fast-acting pharmacological approaches that target the GABAergic system to treat MDD. We conclude that deficits in cortical inhibitory neurotransmission and interneuron function resulting from chronic stress exposure can compromise the integrity of neurocircuits and result in the development of MDD and other stress-related disorders. Drugs that can establish a new E:I balance in the PFC by targeting the glutamatergic and GABAergic systems show promising as fast-acting antidepressants and represent breakthrough strategies for the treatment of depression.